Comparative analysis of customs valuation methods in CIS countries (Horizon Multidisciplinary Scientific Journal, 2026)
This article comparatively analyzes the methods of customs valuation within the Commonwealth of Independent States (CIS) under selected legal frameworks. The study focuses on the unified customs law framework of the Eurasian Economic Union (EAEU), the national methodology of the Republic of Azerbaijan, and the Customs Code of the Republic of Uzbekistan. The analysis demonstrates that all of these systems are based on the principles of the WTO Agreement on Customs Valuation and recognize six primary methods for determining customs value: the transaction value of imported goods, the transaction value of identical goods, the transaction value of similar goods, the deductive value method, the computed value method, and the fallback (residual) method. At the same time, differences among these countries are observed mainly in the legal institutionalization of these methods, documentation requirements, consultation mechanisms between customs authorities and declarants, the application of provisional or conditional customs values, as well as the degree of flexibility allowed in the use of the fallback method. While the EAEU model is characterized by supranational harmonization, the methodological and administrative mechanisms applied at the national level are more pronounced in Azerbaijan and Uzbekistan. The article concludes that the principal differences within the CIS region lie not in the number of customs valuation methods, but rather in their implementation techniques and governance mechanisms.
Keywords: customs value; CIS countries; EAEU; Azerbaijan; Uzbekistan; WTO; customs valuation; comparative analysis